2018
DOI: 10.1111/cch.12588
|View full text |Cite
|
Sign up to set email alerts
|

The 12‐year prevalence and trends of childhood disabilities in Australia: Findings from the Survey of Disability, Aging and Carers

Abstract: With the anticipated rise in psychological related disability among Australian children, there is a need to ensure availability of a flexible and responsive model of service delivery for this population. This also implies that respite service coverage may need to be substantially increased to meet children and caregivers' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…Compared with other countries, the prevalence of DD among Taiwanese children in the 0–2 y group in 2001 (1.9%) was only one sixth the prevalence among US children at 9 and 24 months of age during the same period (13.0%) (Rosenberg et al, 2008). The prevalence of DD among children 0–4 y group increased between 2003 (2.8%) and 2015 (4.9%) in present study, whereas study in 2015 in Australia (Arabiat et al, 2018) found prevalence among children in the 0–4 y varied slightly between 2003 (4.3%) and 2015 (3.5%). In this study, the prevalence of DD among children in the 0–5 y group increased between 2000 (2.0%) and 2014 (5.5%).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Compared with other countries, the prevalence of DD among Taiwanese children in the 0–2 y group in 2001 (1.9%) was only one sixth the prevalence among US children at 9 and 24 months of age during the same period (13.0%) (Rosenberg et al, 2008). The prevalence of DD among children 0–4 y group increased between 2003 (2.8%) and 2015 (4.9%) in present study, whereas study in 2015 in Australia (Arabiat et al, 2018) found prevalence among children in the 0–4 y varied slightly between 2003 (4.3%) and 2015 (3.5%). In this study, the prevalence of DD among children in the 0–5 y group increased between 2000 (2.0%) and 2014 (5.5%).…”
Section: Discussioncontrasting
confidence: 61%
“…Estimates of the CWDD prevalence vary considerably among countries and studies, the lowest estimate was 0.16% (Kuo et al, 2015), medium estimates were in the range of 1.5%–7.6% (Arabiat et al, 2018; Blanchard et al, 2006; Chu, 2005; Demirci & Kartal, 2016; Kuo et al, 2015; Lai et al, 2011; New Taipei City, 2019; Office of Special Education and Rehabilitative Services, 2010), and the highest estimate was 13.0% (Rosenberg et al, 2008). In Taiwan, the prevalence rate was 1.6% based on CWDD national registry (Ministry of Health and Welfare, R.O.C., 2018) and 3.5% based on educational statistics (Ministry of Education, R.O.C., 2016) in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…For children born to mothers with diabetes, interventions should focus on maintaining glycaemic control and optimum weight during pregnancy in order to ensure children's improved motor development. It is penitent also for policy makers to consider these variables when thinking about strategies to cope with the increased complexity and new challenges posed by the number of children appears to have developmental delay [42].…”
Section: Discussionmentioning
confidence: 99%
“…According to the most recent data on people with a disability from the ABS, the prevalence of any developmental disability in Australia increased from 6.9-7.42% between 2009 and 2015; but this did not specify the types of childhood disabling conditions. 31 We know child disability is common, but robust current estimates to inform planning and service provision are entirely lacking. Available data sources were incomplete and inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…7 Childhood developmental disability is just under 10%, based on the survey data from the United Kingdom, 8 United States, 6 and Australia. 9 There are complexities in estimating the prevalence of developmental disability as the diagnostic criteria for ASD and other childhood disabilities have changed with the Diagnostic and Statistical Manual-5 released in 2013, 10 and the International Classi cation of Disease 11 in 2018. 11 National data on disability in Australia from 2012 and subsequently from 2018 by the Australian Bureau of Statistics (ABS) noted that the children with intellectual impairments, and sensory and speech disorders, as the most common reasons for children with disabilities.…”
Section: Introductionmentioning
confidence: 99%